Wacana Drama Korea dalam Iklan Sprite Versi “Kenyataan Gak Kayak Drama Korea” - Shani Fella; Fitri Murfianti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2019)
The development of the Hallyu, or Korean Wave, has an impact on product advertising in Indonesia, which uses many actors and discourses brought from Korean culture.Starting from this it turns out that growing questions about the possibility of Korean Wave can shape new consumption interests and behaviors that have an interest in Korea. The study, entitled Korean Drama Discourse in the Sprite ad version “Kenyataan Gak Kayak Drama Korea” is an advertisement for Sprite beverage products identified using Korean drama discourse with humor at the end of the story. The research method used is descriptive qualitative research supported by a theoretical basis, namely the structure of advertising discourse to dismantle Korean drama discourse on the Sprite advertisement version “Kenyataan Gak Kayak Drama Korea” using the concept of fashion as communication and storyline and location settings to be peeled off per scene advertisement. The discourse structure of advertising in this study will be explained in three parts, namely the main items of advertising, advertising agencies and closing advertisements. The results of this study indicate that in the version of the Sprite advertisement “Kenyataan Gak Kayak Drama Korea” there is a Korean drama discourse displayed on the advertising body, which functions as an advertisement explanatory item that is a message from a Sprite advertisement that "Nyatanya Nyegerin" can be well received by prospective customers.